Influences of fuel concentration, fuel volume, initial temperature, and initial pressure on flame propagation and flameproof distance of methane-air deflagrations. Issue 6 (1st August 2016) - Jiang, Bingyou; Liu, Zegong; Shi, Shulei; Cai, Feng; Liu, Jian; Tang, Mingyun; Lin, Baiquan
Abstract : Purpose: Understanding a flameproof distance necessary to avoid the flame harms to underground personnel may have great significance to the safety of underground personnel and the disaster relief of gas explosions in coal mines. Design/methodology/approach: Through a roadway with a length of 100m and a cross-section area of 80mm×80mm, the flame propagation of premixed methane-air deflagrations were simulated by using AutoReaGas software for various fuel concentrations (7%, 8%, 9.5%, 11%, and 14%), fuel volumes (0.0128m3, 0.0384m3, 0.064m3, and 0.0896m3), initial temperatures (248K, 268K, 288K, 308K, and 328K), and initial pressures (20kPa, 60kPa, 101.3kPa, 150kPa, and 200kPa). Findings: The maximum combustion rate for each point follows a changing trend of increasing and decreasing with the distance increasing from the ignition source, and it increases with the fuel volume increasing or the initial pressure increasing, and decreases with the initial temperature increasing. However, increasing the initial temperature increases the flame arrival time for each point. The flameproof distance follows a changing trend of increasing and decreasing with the fuel concentration increasing, and it linearly increases with the fuel volume increasing or the initial temperature increasing. However, the flameproof distances are all 17m for various initial pressures. Originality/value: Increasing initial temperature increases flame arrival time for each test point. Flameproof distance increases and then decreases with fuel concentration increasing. Increasing fuel volume or initial temperature linearly increases flameproof distance. Initial pressure has little impact on the flameproof distance.